Handball Performance Optimization: Anthropometric and Physical Factors Related with Shoot Speed - Lagunes-Carrasco, José Omar; López-García, Ricardo; Navarro-Orocio, Ricardo; Hernández-Cortes, Perla Lizeth; Ramírez-López, Erik; Reynoso-Sanchez, Luis Felipe; Barajas-Pineda, Lenin Tlamatini (International Journal of Sport Studies for Health, 2025)
Objective: This study aimed to analyze the relationship between ball throwing speed and anthropometric variables, body composition, and hand grip strength in male and female handball players across three age categories: U-16, U-18, and U-21.Methods and Materials: A total of 226 players (109 males, 117 females) from four Mexican regions were assessed using a cross-sectional, descriptive-correlational design. Anthropometric measurements followed ISAK protocols, while body composition was assessed via bioelectrical impedance. Segmental lengths, grip strength, and throwing speed from 7 meters were also evaluated. Statistical analyses included ANOVA, t-tests, and stepwise linear regression. Results indicated age-related improvements in fat-free mass, grip strength, and throwing speed, particularly in U-21 players.Findings: Males exhibited significantly greater height, lean mass, and performance metrics compared to females. Regression analysis revealed that arm length and grip strength significantly predicted throwing speed in males, while grip strength, fat percentage (negative), and BMI were significant predictors for females. Age-stratified analyses highlighted that arm length predicted speed in U-16 males, body weight in U-18 males, and grip strength in U-21 athletes of both sexes.Conclusion: These findings underscore the importance of strength and specific anthropometric traits in throwing performance and suggest the need for age- and sex-specific training strategies to optimize development. The study supports incorporating tailored conditioning programs to enhance handball players’ throwing ability based on developmental and physical profiles.